Interrelationship of the volunteerism and solidarity concepts in sociology - O. P. Noskova (Вестник университета)
The article presents the results of theoretical and empirical research into interrelationship of the volunteerism and solidarity concepts in sociology, and the former has been considered as a form of assistance and support for those in need, and the latter as an ideological justification of this assistance, a link that allows citizens to rally around a common good goal. Both concepts, being direct attributes of civil society, allow to strengthen social ties and promote formation of indifferent attitude to social transformations. Theoretical and methodological basis of the study was formed by the approaches of domestic and foreign authors such as M. Weber, E. Durkheim, P. Sorokin, T. Parsons, A. Schütz, D. Alexander, P. Kropotkin, V. Lenin, K. Biderman, V. Jeffries, T. Lisovskaya, I. Mersiyanova, L. Yakobson, M. Pevnaya, G. Bodrenkova, and T. Nezhina. The most popular motives for engaging in volunteer activities have been analyzed, and various approaches to the definition of the volunteerism and solidarity concepts have been considered. The associative survey and content analysis of search queries on the “volunteerism” and “solidarity” words-markers have been conducted, and on their basis a scheme of their interrelationship and a synquain as a consequence of their logical dependence have been drawn up. As a result of two concepts of sociological science comparison such as volunteerism and solidarity it has been established that they are inseparable, and volunteer activity is a consequence of social solidarity. The necessity of forming stable links between a joint idea and action, which contributes to strengthening of social ties among people and civil society development, has been substantiated.